Electricity Safety Analysis and Improvement Based on User Classification - Zhu Hongxia; Wang Qing; Li Congcong; Du Yan; Yu Chao (E3S Web of Conferences, 2020)
Analyzing electricity consumption behavior by classifying user groups and knowing each group’s characteristics are an important way to realize intelligent power consumption. This paper firstly classifies different types of users based on power consumption data and grasps the power consumption behavior of typical users. The main causes of accidents and alarms are then discussed based on the recorded events and power consumption curve. Finally, the corresponding solutions, which take the user’s social attributes and electricity consumption behavior into consideration are put forward to avoid the potential accidents.